Insecticide-treated clothes for the control of vector-borne diseases: a review on effectiveness and safety - Banks, Sarah D.; Murray, N.; Wilder-Smith, Annelies; Logan, J. G. (Medical and veterinary entomology, 2014)
Insecticide-treated clothing has been used for many years by the military and in recreational activities as personal protection against bites from a variety of arthropods including ticks, chigger mites, sandflies and mosquitoes. Permethrin is the most commonly used active ingredient, but others, including bifenthrin, deltamethrin, cyfluthrin, DEET (N,N-diethyl-3-methylbenz-amide) and KBR3023, have also been trialled. Treatment is usually carried out by home or factory dipping. However, new microencapsulation technologies which may prolong the activity of insecticides on clothing are now available and may help to overcome the inevitable reduction in efficacy over time that occurs as a result of washing, ultraviolet light exposure, and the normal wear and tear of the fabric. The aim of this article is to review the evidence base for the use of insecticide-treated clothing for protection against bites from arthropods and its effect on arthropod-borne pathogen transmission. Although some studies do demonstrate protection against pathogen transmission, there are surprisingly few, and the level of protection provided varies according to the disease and the type of study conducted. For example, insecticide-treated clothing has been reported to give between 0% and 75% protection against malaria and between 0% and 79% protection against leishmaniasis. Studies vary in the type of treatment used, the age group of participants, the geographical location of the study, and the pathogen transmission potential. This makes it difficult to compare and assess intervention trials. Overall, there is substantial evidence that insecticide-treated clothing can provide protection against arthropod bites. Bite protection evidence suggests that insecticide-treated clothing may be useful in the prevention of pathogen transmission, but further investigations are required to accurately demonstrate transmission reduction.